2010
DOI: 10.1523/jneurosci.2098-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin Directly Excites Anorexigenic Proopiomelanocortin Neurons but Inhibits Orexigenic Neuropeptide Y Cells by an Indirect Synaptic Mechanism

Abstract: The neuropeptide kisspeptin is necessary for reproduction, fertility, and puberty. Here, we show strong kisspeptin innervation of hypothalamic anorexigenic proopiomelanocortin (POMC) cells, coupled with a robust direct excitatory response by POMC neurons (n Ͼ 200) to kisspeptin, mediated by mechanisms based on activation of a sodium/calcium exchanger and possibly opening of nonselective cation channels. The excitatory actions of kisspeptin on POMC cells were corroborated with quantitative PCR data showing kiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
193
2
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(216 citation statements)
references
References 94 publications
13
193
2
8
Order By: Relevance
“…There is strong evidence that kisspeptin would decrease food intake and increase energy expenditure, resulting in a decrease in body weight. In one electrophysiological study, kisspeptin has been shown to directly excite POMC/ CART neurons and indirectly inhibit NPY/AgRP neurons (Fu & van den Pol 2010). Our finding that central administration of kisspeptin causes decreases in food intake and body weight is consistent with the results of this Action of RF9 is dependent on kisspeptin signaling electrophysiological study.…”
Section: Central Administration Of P234 Inhibits Kisspeptininduced Fosupporting
confidence: 90%
See 1 more Smart Citation
“…There is strong evidence that kisspeptin would decrease food intake and increase energy expenditure, resulting in a decrease in body weight. In one electrophysiological study, kisspeptin has been shown to directly excite POMC/ CART neurons and indirectly inhibit NPY/AgRP neurons (Fu & van den Pol 2010). Our finding that central administration of kisspeptin causes decreases in food intake and body weight is consistent with the results of this Action of RF9 is dependent on kisspeptin signaling electrophysiological study.…”
Section: Central Administration Of P234 Inhibits Kisspeptininduced Fosupporting
confidence: 90%
“…The modulatory effects of RFRP on kisspeptin are important in terms of not only reproductive functions but also nutritional aspects. For example, functional electrophysiological analyses have documented the ability of RFRP-3 to inhibit the excitatory actions of kisspeptins on pro-opiomenalocortin (POMC) neurons (Fu & van den Pol 2010). Therefore, in the present experiment, the importance of the interaction between kisspeptin and RFRP was also investigated in terms of energy metabolism.…”
Section: Introductionmentioning
confidence: 94%
“…These neurons may possess Kiss1r because it is expressed in cells within the ARC (Lee et al 1999), which are not kisspeptin neurons . Moreover, electrophysiological recordings in mice show that kisspeptin can directly excite POMC/CART neurons and indirectly inhibit NPY/ AgRP neurons, via a mechanism based on enhancing GABA-mediated inhibitory synaptic tone (Fu & van den Pol 2010). The net effect of such kisspeptin regulation would be to decrease food intake and increase metabolism.…”
Section: Pomc/cart Neuronsmentioning
confidence: 99%
“…There are neuroanatomical and functional connections between kisspeptin and important hypothalamic appetite‐regulating neuropeptides 15, 16, 17. Intracerebroventricular administration of kisspeptin has been reported to alter food intake in mice18 and chicks,19 while other studies report no effect of kisspeptin administration on appetite in rats 20.…”
Section: Introductionmentioning
confidence: 99%